Bio‐based polyurethane films using white dextrins. Issue 20 (8th January 2019) - Konieczny, Jakob; Loos, Katja
ABSTRACT: Several new eco‐friendly materials have the potential to replace conventional petroleum‐derived materials and monomers. Among them are natural polysaccharides. The use of polysaccharides in polyurethane (PU) synthesis has not yet been studied extensively, even though as multihydroxyl compounds, they can easily serve as crosslinkers in PU synthesis. One naturally occurring (hyper‐)branched polymer is amylopectin, a component of starch. In this work, we report the PU synthesis and film‐forming capacity using the asymmetric cyclic aliphatic diisocyanate—isophorone diisocyanate (IPDI) with acetylated and pristine partially hydrolyzed amylopectin/white dextrin (AVEDEX W80) as a crosslinker. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47454. Abstract :